2018
DOI: 10.1002/cptc.201800104
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Emission and Light‐Induced Charge Separation in Colloidal ZnO Nanocrystals

Abstract: Adsorption of organic molecules at ZnO nanoparticle surfaces enables the transfer of energy or charge across resulting organic–inorganic interfaces and, consequently, determines the optoelectronic performance of ZnO‐based hybrids. We investigated adsorption‐induced changes with photoluminescence (PL) and electron paramagnetic resonance (EPR) spectroscopy on aqueous colloidal ZnO dispersions. Citrate and acetate ion adsorption increases or decreases radiative exciton annihilation at hν=3.3 eV and at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…With this very first systematic comparison of the free exciton emission of ZnO nanocrystals, which were grown in the gas phase, processed, and measured under water-free conditions, with identical nanoparticles in contact with a condensed water phase, we discuss important optical property changes that can originate from the conversion of the anhydrous powder into an aqueous colloidal dispersion. The present investigation connects to a previously performed study on aqueous ZnO colloids that aimed at the relationship between adsorption-induced photoluminescence property changes and the yield of photogenerated charges that are accessible to electron paramagnetic resonance spectroscopy . Here, we used two widely employed surfactants, citrate ions producing negative ζ-potential values, and acetate ions, the adsorption of which shifts the corresponding ζ-potential values to more positive values.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…With this very first systematic comparison of the free exciton emission of ZnO nanocrystals, which were grown in the gas phase, processed, and measured under water-free conditions, with identical nanoparticles in contact with a condensed water phase, we discuss important optical property changes that can originate from the conversion of the anhydrous powder into an aqueous colloidal dispersion. The present investigation connects to a previously performed study on aqueous ZnO colloids that aimed at the relationship between adsorption-induced photoluminescence property changes and the yield of photogenerated charges that are accessible to electron paramagnetic resonance spectroscopy . Here, we used two widely employed surfactants, citrate ions producing negative ζ-potential values, and acetate ions, the adsorption of which shifts the corresponding ζ-potential values to more positive values.…”
Section: Introductionmentioning
confidence: 70%
“…In the present case, namely, there is no correspondence between adsorbate-induced intensity changes related to the free exciton emission at λ = 380 nm and the broad emission band centered at λ = 670 nm, the intensity of which remains constant throughout all of the experiments performed for this study and which therefore is also not correlated with the observed ζ-potential changes. Hence, under the experimental conditions, applied citrate and acetate adsorption have no significant influence on potential energy transfer steps that convert a fraction of the exciton energy into a defect-related emission in the visible light range …”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations